Efficient transmission of tick-borne encephalitis virus between cofeeding ticks - Labuda, M; Jones, L D; Williams, T; Danielova, V; Nuttall, P A (Journal of medical entomology, 1993)
Most of the data on oral infections of ticks with tick-borne encephalitis virus have been derived from experiments using animals infected by syringe inoculation. To mimic the natural conditions of virus transmission, tick-borne encephalitis virus-infected Ixodes ricinus (Linnaeus) or Rhipicephalus appendiculatus Neumann adults (donors) were cofed with uninfected nymphs (recipients) of either tick species on uninfected guinea pigs. Two tick-retaining cells were attached to each guinea pig: cell 1 contained uninfected nymphs and virus-infected adults, and cell 2 contained uninfected nymphs. Following engorgement, 55% of I. ricinus nymphs and 65% of R. appendiculatus nymphs were shown to have acquired the virus while cofeeding with I. ricinus donor ticks. Similarly, 66% of R. appendiculatus recipient nymphs that cofed with R. appendiculatus virus-infected adults were infected. Some of the guinea pigs on which the ticks cofed were apparently nonviremic. The results indicate that efficient transmission of tick-borne encephalitis virus can occur between cofeeding ticks even when the host on which they feed does not develop a detectable viremia.
Keywords: Animals; Arachnid Vectors; klíšťata; Mice; Nymph; Ticks; zvířata; ženské pohlaví; myši; Encephalitis Viruses, Tick-Borne; arachnida jako vektory; viry klíšťové encefalitidy; nymfa; Female; Guinea Pigs; morčata; Male; mužské pohlaví